Hispanic-Serving Institutions as Racialized Organizations: Elevating Intersectional Consciousness to Reframe the "H" in HSIs - Blanca Elizabeth Vega; Román Liera; Mildred Boveda (SAGE Publishing, 2022)
Conceptualizations of servingness must include an understanding of how racial ideologies shape Hispanic-Serving Institutions (HSIs). Three Latinx scholars offer testimonios on our experiences as students, faculty, and researchers at teaching and research-intensive HSIs. From our testimonios, we found that practices of Blanqueamiento (Whitening of a population) and Mestizaje (racial mixture) operate at HSIs to flatten our understanding of Hispanics in U.S. society. To make sense of our testimonios within these HSI contexts and constraints, we applied an intersectional consciousness perspective on racialized organizations. Findings include Whiteness operating as a credential, legitimizing unequal resources, diminishing agency among minoritized groups, and continued use of Mestizaje (disguised as Hispanic) as a prevailing ideology. We provide considerations for HSI leaders, researchers, and administrators to elevate their intersectional consciousness and disrupt how HSIs contribute to essentialist notions of Latinxs.